2021
DOI: 10.1111/cas.14814
|View full text |Cite
|
Sign up to set email alerts
|

CircPVT1 promotes progression in clear cell renal cell carcinoma by sponging miR‐145‐5p and regulating TBX15 expression

Abstract: Renal cell carcinoma (RCC) is one of the most common cancers worldwide and is often asymptomatic in an early stage. 1,2 Clear cell RCC (ccRCC) is the most common histological type and accounts for about 75% of RCCs. 3 As ccRCC is insensitive to radiotherapy and chemotherapy, surgical resection is considered the best treatment for ccRCC patients. However, about 30% of localized ccRCC patients receiving surgical treatment subsequently developed metastatic disease that proved to be fatal. 4 Despite continued effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…They found that circPVT1 expression was significantly increased in patients’ serum. Moreover, they found that circPVT1 explicates its tumorigenic activity by directly interacting with miR-145-5p leading to the upregulation of one of its targets TBX15 (T-Box Transcription Factor 15), associated with the progression of RCC [ 71 ]. Intriguingly, other recent study by Zheng X. and colleagues revealed that circPVT1 is associated with medullary thyroid cancer, sustaining the metastatic process by acting on miR-455-5p/CXCL12/CXCR4 signaling axis [ 71 ].…”
Section: The Circpvt1/lncpvt1/c-myc Oncogenic Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that circPVT1 expression was significantly increased in patients’ serum. Moreover, they found that circPVT1 explicates its tumorigenic activity by directly interacting with miR-145-5p leading to the upregulation of one of its targets TBX15 (T-Box Transcription Factor 15), associated with the progression of RCC [ 71 ]. Intriguingly, other recent study by Zheng X. and colleagues revealed that circPVT1 is associated with medullary thyroid cancer, sustaining the metastatic process by acting on miR-455-5p/CXCL12/CXCR4 signaling axis [ 71 ].…”
Section: The Circpvt1/lncpvt1/c-myc Oncogenic Networkmentioning
confidence: 99%
“…Moreover, they found that circPVT1 explicates its tumorigenic activity by directly interacting with miR-145-5p leading to the upregulation of one of its targets TBX15 (T-Box Transcription Factor 15), associated with the progression of RCC [ 71 ]. Intriguingly, other recent study by Zheng X. and colleagues revealed that circPVT1 is associated with medullary thyroid cancer, sustaining the metastatic process by acting on miR-455-5p/CXCL12/CXCR4 signaling axis [ 71 ]. CircPVT1 results to be involved also in gall bladder cancer (GBC) where Wang S. and colleagues demonstrated that it is upregulated and promotes proliferation, migration and invasion as well as inhibits cell apoptosis acting as a miRNA sponge for miR-339-3p thus upregulation its target MCL-1 (myeloid cell leukemia-1) which is an anti-apoptotic protein involved in cancer progression [ 73 ].…”
Section: The Circpvt1/lncpvt1/c-myc Oncogenic Networkmentioning
confidence: 99%
“…For instance, the miR-19b-3p released in ccRCC by exosomes in the microenvironment is responsible for both activating EMT via r PTEN and cross talking with long distant niches to favor metastasis [145]. The circular RNA, named circPVT1, is upregulated in ccRCC tissue according to the histopathology [146]. CircPVT1 directly binds the miR-145-5p.…”
Section: Deregulation Of Mirnas In Ccrcc Tissuementioning
confidence: 99%
“…Finally, miR-199a-5p and miR‐145‐5p have been identified as targets of circPVT1 in glioblastoma ( 39 ) and clear cell renal cell carcinoma ( 40 ), respectively.…”
Section: In Vitro Studiesmentioning
confidence: 99%